Plan Colombia. Approved by the United States Senate on Friday, July 23, 2000 - de Estados Unidos, Gobierno (2016)
The Colombian government developed the Plan Colombia as an integrated strategy to face the most pressing challenges currently facing the country: promoting the peace process, fighting the drug trafficking industry, reviving the Colombian economy and strengthening the democratic pillars of Colombian society. Plan Colombia is 7.5 billion dollars program. President Pastrana has already committed $ 4 billion in Colombian resources and has called on the international community to contribute the remaining $ 3.5 billion to complete this effort.